The physical activity interventions for children in school-based setting: a scoping review - Abdullah, Ammar Syahmi (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Background: The population of Malaysia faces an increased burden of overweight and obese leading to many health chronic disease. Physical activity is inversely associated with several health outcomes in adults while physical activity has been reported to confer various benefits on children’s physical and psychological state. School is proven to be a suitable setting for programe of intervention that aim to promote physical activity for health benefit. Aim: The objective of this scoping review is to study the physical activity intervention of children in school-based settings. This study also investigate the improvements of health and mood after physical activity intervention and determine the effectiveness of the physical activity intervention of children in a school-based setting. Method: Ebscohost, Springer Link, Scopus and Science Direct were searched for peer reviewed journal articles. Inclusion criteria were studies that examined a physical activity intervention of children aged 7-18 in school based settings and the search process was from 2016-2021. 21 studies met the inclusion criteria and all were eligible for in this study. Results: 17 of the studies show a significant changes while 4 others did not manage to produce a significant result. the physical activity intervention also manage to improve children mood and health. Conclusion: This review provides strong evidence that some physical activity interventions can have a significant result on children’s overall activity level. This finding may explain, in part, why such interventions have had limited success in increasing physical activity.